Environmental aspect in traffic flow simulation modeling - Krasnikov, Aleksandr; Mironov, Pavel (E3S web of conferences, 2024)
The article deals with the problem of air pollution by automobile transportation. Such emissions are a problem in modern cities worldwide, and they harm numerous aspects of human life and the environment. Changing traffic flows and modernization of road infrastructure are ways to reduce the load on the ecological state of urban areas. Developing concepts and assessing their impact on the transportation system and the environment is possible through simulation models. The study establishes all the objects and their qualitative and quantitative characteristics necessary to create a digital twin of traffic flows. Using parametric modeling techniques allowed us to create a simulation model reflecting all aspects of the subject area. The developed model allows conducting experiments on changing the parameters of objects to predict changes in the system’s behavior in terms of its ecological state.